Telomere Length and Accelerated Biological Aging in the China Suboptimal Health Cohort: A Case-Control Study - Alzain, M. A.; Asweto, Collins O.; Zhang, J.; Fang, H. H.; Zhao, Z.; Guo, X.; Song, M.; Zhou, Y.; Chang, N.; Wang, Y.; Wang, W. (Mary Ann Liebert, Inc, 2017)
Suboptimal health status (SHS) has been linked to cardiovascular risk factors, psychosocial stress, and unhealthy lifestyle. These factors also contribute to the shortening of telomere length (TL). A case–control study was conducted to examine the association between subjective health measures of SHS from the behavior perspective and also objective measures of TL at molecular level. SHS (cases = 294) was matched by age, sex, and body mass index with ideal health (controls = 294) using a propensity score matching method. Suboptimal health status questionnaire-25 (SHSQ-25) was used in the community-based health survey. A quantitative polymerase chain reaction was used to measure relative telomere length (RTL). Shorter RTL was found among the SHS group compared to the ideal health group ( p < 0.05). SHS was almost four times likely to be in the first quartile (odds ratio [OR] = 3.81; 95% confidence interval [CI] 2.21–6.56), almost thrice in second quartile (OR = 2.84; 95% CI 1.65–4.90), and almost twice likely to be in the third quartile (OR = 1.71; 95% CI 1.00– 2.94) compared to the fourth quartile (the longest) of RTL after adjusting for socioeconomic, dietary intake, anthropometric, blood pressure, and biochemistry variables ( p < 0.05). Notably, SHS score was negatively correlated with RTL (r=-0.218, p < 0.05). Our study confirms an association between SHS and short RTL. Combination of subjective (SHS) and objective (RTL) measures is a novel tool for health aging investigation. Therefore, SHSQ-25 could be used as a screening tool for measuring biological aging in low-income countries at community level where the expensive technique for RTL measurement is not applicable.
Keywords: suboptimal health status; relative telomere length; China suboptimal health cohort study